1996
DOI: 10.1152/ajprenal.1996.271.4.f886
|View full text |Cite
|
Sign up to set email alerts
|

Permeability properties of the intact mammalian bladder epithelium

Abstract: Because the mammalian bladder must store urine of composition which differs markedly from that of plasma for prolonged periods, the bladder permeability barrier must maintain extremely low permeabilities to substances which normally cross membranes relatively rapidly, such as water, protons, and small nonelectrolytes like urea and ammonia. In the present studies, permeabilities of the apical membrane of dissected rabbit bladder epithelium to water, urea, ammonia, and protons were measured in Ussing chambers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
193
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(205 citation statements)
references
References 0 publications
10
193
2
Order By: Relevance
“…The exceptionally high transepithelial resistance of urothelium results from a high apical plasma membrane transcellular resistance combined with paracellular resistance of tight junctions. 32,33 In the present study, we found that the superficial UCs on sAM were the largest and displayed molecular (uroplakins, occludin) and ultrastructural properties (urothelial plaques, microridges, well-developed tight junctions, and membrane overlaps) of superficial UCs in highly differentiated urothelia. Furthermore, we found that the size of UCs correlated with their differentiation stage, that is, small UCs were less differentiated than larger UCs, which showed properties of highly differentiated UCs.…”
Section: Fig 4 the Distribution Of Urothelial Differentiation-relatsupporting
confidence: 51%
“…The exceptionally high transepithelial resistance of urothelium results from a high apical plasma membrane transcellular resistance combined with paracellular resistance of tight junctions. 32,33 In the present study, we found that the superficial UCs on sAM were the largest and displayed molecular (uroplakins, occludin) and ultrastructural properties (urothelial plaques, microridges, well-developed tight junctions, and membrane overlaps) of superficial UCs in highly differentiated urothelia. Furthermore, we found that the size of UCs correlated with their differentiation stage, that is, small UCs were less differentiated than larger UCs, which showed properties of highly differentiated UCs.…”
Section: Fig 4 the Distribution Of Urothelial Differentiation-relatsupporting
confidence: 51%
“…Many of the structural and functional changes associated with human bladder pathology such as neurogenic inflammation and increased mast cell count can be reproduced in a model of HCl-induced chronic irritation 12,13 . Damaged bladder epithelial layer in IC patients leads to bladder irritation from toxins which causes pain and decreased bladder capacity 14,15 . Similarly, the HCl treatment strips off the upper layers of urothelium and weakens the connections between urothelium and stroma 16 .…”
Section: Discussionmentioning
confidence: 99%
“…This impermeability is attributed to tight junctions between the apical membrane cells and is most effective at preventing absorption of ionized molecules, as found in the urine. 46 Mishina et al 47 showed that absorption of a weak base molecule was profoundly affected by pH of the bladder content and was optimal at pH >6. Because the route of entry is considered to be directly transmembranal, rather than between cells, lipid solubility (partition coefficient) and molecular size were also shown to be important determinants for the absorption of substances through the bladder epithelium.…”
Section: Permeability Of Bladder Epitheliummentioning
confidence: 99%